Pengembangan Pendidikan Agama Islam melalui Budaya Religius di Sekolah Menengah Atas di Wonosobo - Mawardi, Kholid; Fatmawati, Julia; Azmi, Aulia; Rohmah, Ummu Lutfiatur; Nurfadilah, Trisna (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2021)
There are several criticisms directed at the learning process of Islamic Religious Education in schools. Some arguments state that Islamic Religious Education learning does not show significant progress in changing student behavior and attitudes. Most critics argue that the learning process of Islamic Religious Education only focuses on the cognitive aspects of students not the affective aspect. This study aims to explore the development model of Islamic Religious Education through religious culture at SMAN 1 Wonosobo. This study tries to provide a comprehensive understanding of the implications of Islamic Religious Education on the transformation of students' religiosity through religious culture. The results of the study show : 1) the development of Islamic Religious Education is formed through activities outside the learning process; 2) activities outside the learning process are designed to become a religious culture consisting of two models. The first is organic-systemic which is based on school policies and the second is the initiative of Islamic Religious Education teachers, 3) the manifestation of student religiosity can be seen from the changing focus of Islamic Religious Education from mastery and understanding of religious teachings to growing self-awareness to form religious attitudes in school.